Healthcare Professionals, Post-traumatic Stress Disorder, and COVID-19: A Review of the Literature - Saladino, Valeria; Auriemma, Vincenzo; Campinoti, Valeria (Frontiers in Psychiatry, 2022)
The recent COVID-19 pandemic impacted healthcare professionals psychologically. They were unprepared to handle such a powerful and unknown virus. Consequently, they had to face situations of extreme distress, developing vicarious traumatization and post-traumatic stress disorder (PTSD). The first one is associated with the “cost of caring” for others and affected persons who constantly are exposed to other sufferings. PTSD is a psychiatric disorder that could affect people who have experienced or witnessed a traumatic event. Post-traumatic stress disorder (PTSD) and correlated symptoms might impact the lives of healthcare professionals at the personal, professional, and relational levels. Furthermore, the pandemic could decrease the empathy of healthcare professionals, influencing their relationship with patients. This review aimed to describe the incidence of PTSD among HPs during the COVID-19 pandemic. We focused on the following aspects: (a) PTSD symptoms and correlated psychological issues; (b) repercussions at working and personal levels; (c) change in empathetic involvement of healthcare professionals.